2005
DOI: 10.1158/0008-5472.can-04-3922
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Mapping of MCF10A Human Breast Cells via Multiphoton Fluorescence Lifetime Imaging of the Coenzyme NADH

Abstract: Biochemical estimation of NADH concentration is a useful method for monitoring cellular metabolism, because the NADH/NAD + reduction-oxidation pair is crucial for electron transfer in the mitochondrial electron chain. In this article, we present a novel method for deriving functional maps of intracellular reduction-oxidation ratio in vivo via measurement of the fluorescence lifetimes and the ratio of free and protein-bound NADH using two-photon fluorescence lifetime imaging (FLIM). Through systematic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
376
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 353 publications
(430 citation statements)
references
References 28 publications
53
376
1
Order By: Relevance
“…The lifetimes of free and protein-bound NADH and their relative contributions measured in vivo in normal tissues are consistent with previous work in cell culture (17,18) and in vivo (19). The fluorescence lifetime of protein-bound NADH and its contribution decreased with precancer development in vivo (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The lifetimes of free and protein-bound NADH and their relative contributions measured in vivo in normal tissues are consistent with previous work in cell culture (17,18) and in vivo (19). The fluorescence lifetime of protein-bound NADH and its contribution decreased with precancer development in vivo (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3a), consistent with the results of a previous study (19). Studies have found that the lifetime of free and protein-bound NADH and the relative contribution of protein-bound NADH decrease with hypoxia in cell culture (17)(18)(19) and tissue slices (20). Under hypoxic conditions, cells favor glycolysis over oxidative phosphorylation for ATP production.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations